Comparative Analysis on the Public Treasury Management Accounting in Romania - Present and Future - - Maria MORARU; Denisa ABRUDAN (Revista de Management Comparat International)
This paper work is making a comparison between current accounting system and cash and accrual accounting system type of the Public Treasury highlighting the main disadvantages and advantages of the application of accrual accounting.